2017
DOI: 10.15406/jdvar.2017.05.00138
|View full text |Cite
|
Sign up to set email alerts
|

Residual Feed Intake, Digestibility of Nutrients and Efficiency of Water Utilizations in Murrah Buffalo Heifers

Abstract: A metabolism trial was conducted for 7d to determine residual feed intake (RFI=measure of the difference between actual feed intake and expected feed requirement), dry matter intake (DMI), digestibility and metabolism of nutrients at the end of a 57 days (d) of a feeding trial with 18 Murrah buffalo heifers (279kg±16; and 684±131d of age). Preliminary selection of heifers as efficient and less efficient was done by regressing actual DMI on predicted DMI (g/head/d) using the model DMI (g/kg BW) = β 0 + β predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(17 reference statements)
1
0
0
Order By: Relevance
“…These results are in accordance with previous studies in which more efficient animals showed a higher nutrient digestibility and a smaller nutrient loss through waste and methane emission (Richardson et al 1996;Nkrumah et al 2006). Negesse et al (2017) also observed improved apparent digestibility coefficients of DM, OM and CP in HE heifers; these animals excreted a smaller proportion of N through faeces and their N biological value (digestible N ratio) was higher than that of less efficient heifers, suggesting that CP digestion and metabolism may be enhanced in HE animals. In comparison, de Assis Lage et al (2019) did not find differences in digestibility coefficients of such nutrients but they reported a tendency of HE heifers to better digest ether extract fraction.…”
Section: Rfi and Mechanisms Underlying The Variability Of Fesupporting
confidence: 93%
“…These results are in accordance with previous studies in which more efficient animals showed a higher nutrient digestibility and a smaller nutrient loss through waste and methane emission (Richardson et al 1996;Nkrumah et al 2006). Negesse et al (2017) also observed improved apparent digestibility coefficients of DM, OM and CP in HE heifers; these animals excreted a smaller proportion of N through faeces and their N biological value (digestible N ratio) was higher than that of less efficient heifers, suggesting that CP digestion and metabolism may be enhanced in HE animals. In comparison, de Assis Lage et al (2019) did not find differences in digestibility coefficients of such nutrients but they reported a tendency of HE heifers to better digest ether extract fraction.…”
Section: Rfi and Mechanisms Underlying The Variability Of Fesupporting
confidence: 93%